Public expenditures allocated to fight COVID-19 in Alagoas, Brazil - Rodrigo dos Santos, Carlos; Fernandes dos Santos, Diane; Maria Pontes Bulhões, Thaynara; Omena de Oliveira, Jayane; Magna de Oliveira Costa, Caroline; Régia Braz Costa, Christefany (Journal of Health Care, 2021)
Introduction: The COVID-19 pandemic has had epidemiologic relevance to the public health system in the state of Alagoas, Brazil. However, few scientific publications approach the economic impact of this pathology. Objective: To describe the allocation of public resources to fight COVID-19 in Alagoas. Methods: This is descriptive research with a quantitative data approach. The expenditures included were related to the provision of food staples, communication, COVID-19 test kits, hospital equipment, ambulances, personal protective equipment, hospital medical supplies, construction, and engineering services. The data was collected from the Transparency Portal of the State of Alagoas in September 2020, based on allocated values. The period analyzed encompassed up to September 5, 2020. Results: It was verified that Alagoas allocated R 39,304,771.41 to buy personal protective equipment, hospital medical supplies, COVID-19 test kits, and hospital equipment. Also, the State allocated the greatest resources to hospital and outpatient assistance, summing R 137,706,530.81, and the lowest ones to training human resources, with R 11,610.90. Also, R 1,008,047.93 were noticeably allocated to epidemiologic surveillance. Conclusions: The State provided resources mainly to elements directly related to health assistance addressing this problem.